Application of Construct on Scaffold Concept Map in Mobile Programming Learning with Flutter Layout Topic - Putra Prima Arhandi; Annisa Taufika Firdausi; Vivin Ayu Lestari; Abdurrasyid Muhasibi; Dharma Yudistira Eka Putra; Banni Satria Andoko (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Flutter is a framework for making mobile applications cross-platform made by Google. From 2019 to 2021 the popularity of flutter is increasing. Flutter use declarative writing style to create layouts. This makes the layout in flutter immutable, and a light blueprint. This research proposes a construct on scaffold concept map method to help students understand the concept of widget arrangement in flutter layout. Construct on scaffold will provide the learner with a framework from an incomplete expert concept map. Some of the nodes and connecting relationships in the framework have been removed, so students must fill in the missing parts with several available answer choices to complete the concept map. To prove the impact of the application of this method, the study was conducted using a pre-post-test group experimental design. Students will do a pre-test, use the EasyFlutter application, and post-test. The results of the pre-test and post-test obtained were tested for normality first, then tested to find out whether there was an average difference between the pre-test and post-test scores. The results of the normality test show that the pre-test data are not normally distributed, and the post-test data are normally distributed, so the next test will use a non-parametric test, namely the Wilcoxon test. The test results show that the post-test mean score is higher than the pre-test mean. Wilcoxon test results also show that the Asymp value. Sig. (2-tailed) of 0.01, so it can be concluded that there is a significant difference between the pre-test and post-test scores. The application of the construct on scaffold method has a significant positive impact on the post-test scores of students related to the concept of widget arrangement in flutter.